Transition metal pincer catalysts for formic acid dehydrogenation: a mechanistic perspective - Kumar, N. Sai; Adhikary, Anubendu (Frontiers in Chemistry, 2024)
Storage and transportation of hydrogen gas, a non-polluting alternative to carbon-based fuels, has always been a challenge due to its extreme flammability. In this regard, formic acid (FA) is a promising liquid organic hydrogen carrier (LOHC) and over the past decades, significant progress has been made in dehydrogenating formic acid (FA) through transition metal catalysis. In this review, our goal is to provide detailed insight into the existing processes to expose various mechanistic challenges associated with FA Dehydrogenation (FAD). Specifically, methodologies that are catalyzed by pincer-ligated metal complexes were chosen. Preference to pincer ligands is given as they provide structural rigidity to the complexes which makes the isolation and analysis of reaction intermediates less challenging, consequently, providing a better mechanistic understanding. In this perspective, the catalytic activity of reported pincer complexes in FAD was overviewed and, more importantly, the catalytic cycles were examined in detail. Further attention was given to the structural modifications, role of additives, reaction medium and their crucial effects on the outcome.